Derivation of ganglioside-specific T cell lines of suppressor or helper phenotype from cerebrospinal fluid of multiple sclerosis patients. - Bellamy, A; Davison, A; Feldmann, M (1986)
In order to investigate the specificity of activated T cells in the cerebrospinal fluid (CSF) of patients with multiple sclerosis (MS), we have cultured cells in the presence of mitogen-free IL-2 but without any antigen. Two T cell lines have been derived and showed specific reactivity to certain purified gangliosides (GM1, GD1a, GD1b and GQ1b). However, responses to other brain and viral antigens were not seen, and neither were T cell lines from peripheral blood lymphocytes (PBL) of normal, MS or other neurological disease patients stimulated by these gangliosides. Release of IL-2 could be detected after incubation of these CSF lines with specific gangliosides. One line exhibited predominantly helper/inducer (T4+) phenotype whilst the other was suppressor/cytotoxic (T8+), and further analysis indicated it could be of the suppressor phenotype. These data may have implications for T cell-induced demyelination in MS.